The Role of High Frequency Trading in Market Volatility and Flash Crashes - Ngosa, Abigail (2015)
High Frequency Trading is a phenomenon that is yet to be completely understood. This research attempts to find the relationship if any between high frequency trading and volatility as well as the relationship between volatility and flash crashes. A lot of empirical evidence has been carried out on high frequency trading since the infamous Flash Crash of May 6th 2010 with an array of conflicting results. Despite this, the question as to how HFT affects volatility and flash crashes is yet to be fully answered. Using both daily and minute data, from 12th March 2014 to 11th August 2014 subdivided into three categories, this paper analyses the relationship using both the EGARCH (1,1) model to analyse if there is any relationship and subsequently the Granger Causality Test to try and determine the direction of the relationship. This paper consequently analyses the significance of these relationships and looks at the current regulatory practices that are in play to curb the issues caused by high frequency trading.